Question

using the increment method or four step rule solve for :

y=(x^3-3x^2+3x-1)^1/3

Answer #1

using increment method or 4 step rule solve for:
y= x-2/x-3 , when x=6

using the increment method or four step rule solve for :
(ax+b)^2

using the increment method or four step rule solve for:
Given s=sqrt of t-2, find ds/dt

6) Cramer’s Rule
Solve each using Cramer’s rule
a) 3x + .5y =10
10x - -y =
-3
b) x + z +y = 12
-x + 3y - z = 2
-2x + z = -2
7) Proofs
Prove the following by induction
1. n3 – n is divisible by 3 for n
>=2
2. . Prove that n! <
nn forn ≥ 2.
Prove directly that:
The sum of an integer and its cube...

a)
Let y be the solution of the equation
y ′ − [(3x^2*y)/(1+x^3)]=1+x^3 satisfying the
condition y ( 0 ) = 1.
Find y ( 1 ).
b)
Let y be the solution of the equation y ′ = 4 − 2 x y
satisfying the condition y ( 0 ) = 0.
Use Euler's method with the horizontal step size h =
1/2
to find an approximation to the value of the function
y at x = 1.
c)
Let y...

2.Use separation of variables to solve (3x^2(1-y^2))/2y with
initial condition y(1)=2.
3.State the solution of the homogeneous ODE with roots of its
characteristic equation of r= 1,1,1,+-7i,3+-5i.
4.Consider the system of linear equations:
2x+6y+z=7
x+2y-z=-1
5x+7y-4z=9
solve this system using: a) Carmer's rule, b)Gauss-Jordan
elimination, c) an inverse matrix.

Use Cramer’s Rule to solve the system. x − 6y = 3 3x + 2y =
1

solve the following systems
x'=3x-y+2 , x(0)=1
y'=-4y , y(0) =2

Solve using Gaussian Elimination with back subsitution:
3x(1) - 2x(2) + x(3) =3
2x(1) + 4x(2) - 2x(3) = 2
4x(1) - 2x(2) - 3x(2) = -12

solve the differential equation
y'=y/x+3x^2+x

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 16 minutes ago

asked 19 minutes ago

asked 31 minutes ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago